Agricultural expansion and environmental degradation in the Sepotuba river basin - Upper Paraguay River basin, Mato Grosso State - Brazil - Leandro, Gustavo Roberto Dos Santos [UNESP]; Rocha, Paulo Cesar [UNESP] (Editora da Universidade Federal de Uberlândia - EDUFU, 2023)
The diverse forms of appropriation generate important changes and impacts in the landscapes. In this sense, the present work aimed to analyze the spatial-temporal evolution of agricultural expansion and environmental degradation indices in the Sepotuba River basin, Upper Paraguay basin. For this purpose, satellite images were georeferenced, classified and processed for the period 1986-2016. The thematic maps were validated with the aid of the Kappa Index and subsidized the evaluation of the changes through the Anthropic Transformation Index (ATI). The results showed that there is a strong relationship between agriculture and the suppression of important extensions of native coverage. In the upper and middle course, Tangará da Serra as a pole that has an important role concerning monocultures. In the low course, Cáceres exerts its influence with the predominance of Livestock. Important phytophysiognomies that make up the Sepotuba river basin were identified - a result of the convergence between the Amazon, Cerrado and Pantanal biomes. The results obtained indicate different degrees of impairment of environmental quality in the Sepotuba River system, according to the expansion of land use and occupation in its sub-basins.
Keywords: Land use; Environmental analysis; Geotechnologies; Sepotuba river; Mato Grosso